Philosophical Reflection on Pancasila as a Source of Digital Ethics in Shaping Good Digital Citizenship - Piki Setri Pernantah; Nana Supriatna; Kokom Komalasari; Siti Nurbayani K; Mutiani Mutiani; Aisiah Aisiah (The Innovation of Social Studies Journal, 2025)
The digital era has significantly transformed social structures, cultural dynamics, and human interactions, presenting novel challenges in the realms of ethics and citizenship. The rapid advancement of digital technology has introduced complex ethical dilemmas, necessitating reflection and adaptation of national values and moral principles. This study explores the philosophical underpinnings of Pancasila as a moral foundation for cultivating good digital citizenship, emphasizing the principles of responsibility, constructive freedom of expression, and active, ethical participation within digital communities. Employing an integrative review methodology, this research examines theoretical perspectives on digital ethics and Pancasila, as well as the assimilation of its core values, drawing from interdisciplinary social science literature. By integrating the philosophical values of Pancasila, digital ethics can be developed to address challenges such as hate speech, hoaxes, and misinformation, thereby creating a healthier and more sustainable digital ecosystem. This study also emphasizes the relevance of Pancasila in shaping responsible digital citizens and strengthening social cohesion in the face of technological advancements.